2014
DOI: 10.1016/j.niox.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin improves endothelial dysfunction and vascular remodeling in 2K-1C hypertensive rats by raising nitric oxide availability and reducing oxidative stress

Abstract: Oxidative stress plays a role in maintaining high arterial blood pressure and contributes to the vascular changes that lead to hypertension. Consumption of polyphenol-rich foods has demonstrated their beneficial role in the prevention and treatment of hypertension. Curcumin (CUR), a phenolic compound present in the rhizomes of turmeric, possesses cardiovascular protective, anti-inflammatory and antioxidant properties. The present study was designed to investigate the protective effect of CUR on 2kidney-1clip (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 50 publications
4
72
1
1
Order By: Relevance
“…40 Cadmium-induced vascular dysfunction and hypertension in mice are effectively attenuated by curcumin treatment in which increased eNOS expression is involved. 27 Boonla et al 41 have demonstrated that curcumin improves vascular remodeling and endothelial dysfunction in hypertensive rats associated with an upregulation of eNOS. Here, we found that curcumin was capable of reversing the inhibitory effect of rapamycin on eNOS expression and was protective against cell injury in RAECs in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…40 Cadmium-induced vascular dysfunction and hypertension in mice are effectively attenuated by curcumin treatment in which increased eNOS expression is involved. 27 Boonla et al 41 have demonstrated that curcumin improves vascular remodeling and endothelial dysfunction in hypertensive rats associated with an upregulation of eNOS. Here, we found that curcumin was capable of reversing the inhibitory effect of rapamycin on eNOS expression and was protective against cell injury in RAECs in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin attenuates oxidative stress induced by hypertension and vascular structural modification in 2kidney-1clip (2k-1c) rats by the elevation of plasma nitrate/nitrite, up-regulation of eNOS expression, down-regulation of p47phox NADPH oxidase and decreased superoxide production in the vascular tissues (Boonla et al, 2014).…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Rats were treated with curcumin 100mg/kg/day by intragastric once daily for 8 days. This dose of curcumin was selected on the basis of existed data (Boonla et al 2014a). (iv) GM+CUR group: rats treated with curcumin (100 mg/kg by gavage) followed by gentamicin for 8 consecutive days.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…CUR has been well recognized as a dietary spice for centuries and its pharmacological activity have been studied in various animal models and clinical investigations which exerts anti-inflammatory and antioxidant effects (Boonla et al 2014b;Wu et al 2014b). In cisplatin-induced nephrotoxicity mice model, renal dysfunction and renal tubular necrosis scores were attenuated by CUR treatment through its anti-inflammatory effects by suppressing the pro-inflammatory factors NF-κB and COX-2 as well as promoting downstream markers Nrf2 and HO-1 in kidney (Sahin et al 2014;Ueki et al 2013).…”
Section: Introductionmentioning
confidence: 99%